Pengaruh Diorama Sebagai Media Interaktif Untuk Mengajarkan Keberagaman Umat Beragama Dalam Pembelajaran PKN SD - Adis Sefhira; Indah Setiawati; Nadia Rismala Dewi (Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research examines the influence of dioramas as interactive media in teaching religious diversity in Elementary School Civic Education. Using a quantitative approach with quasi-experimental design and pretest-posttest control group design, the research involved an experimental group learning with interactive dioramas and a control group using conventional methods. The results showed significant differences between the two groups after treatment, with the experimental group's posttest mean score of 82.73 compared to the control group's 69.56 (t=5.678; p<0.05). N-Gain Score analysis showed the experimental group achieved 0.59 (medium category) while the control group only 0.28 (low category). Student responses to diorama usage were highly positive (86.7%), with the highest aspects being visual appeal (92.3%), ease of understanding material (88.7%), and increased learning motivation (87.5%). Interactive dioramas proved effective in concretizing abstract concepts of religious diversity, accommodating various learning styles, enhancing collaborative interactions among students, and developing positive attitudes toward diversity within meaningful and contextual learning environments